Aplikasi Mobile Augmented Reality untuk Mendukung Pengenalan Aksara Sunda - Muhamad Imam Ilham; Yuli Asriningtias (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Currently, the Sundanese script is slowly being ignored by the community, especially children, because of a lack of knowledge about the recognition of the letter. This script is only taught in schools with conventional models, thus making some children feel bored and less interested in learning Sundanese script. Augmented reality (AR) technology can now be utilized in the field of education. The purpose of this study is to build an AR application of Sundanese script using the marker-based tracking method to attract the interest of the community and children in learning Sundanese script. This application is made using Unity software. This research is development research using the Software Development Life Cycle (SDLC) Waterfall model. The stages carried out are the stages of analysis, design, implementation, and finally testing. Our findings are Sundanese AR applications using the marker-based tracking method. In this application, there are features like Main, Marker, Guide, History, and Quiz. The results of black box testing show in all features are working properly. Eligibility results with questionnaire instruments obtained an average percentage of 88.9% from 182 respondents who fell into the very feasible category. So, from previous research, the application was successfully developed with the Sundanese script Ngalagena, Swara, Angka, Rarangken and the history of Sundanese script and practice questions.